2009
DOI: 10.2527/jas.2008-1002
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of real-time ultrasound measurements of total tissue, fat, and muscle depths at different measuring sites in lamb1

Abstract: Accuracy of live ultrasound measurements to evaluate the total tissue depth (GR), as well as fat and LM depths at different scanning sites, was studied in 96 purebred Suffolk and Dorset lambs of both sexes slaughtered between 36 and 54 kg of BW. Before slaughter, 7 real-time ultrasound measurements were taken on lambs: fat and LM depths between the 12th and 13th ribs (transverse) and between the 3rd and 4th lumbar vertebrae (transverse and longitudinal), and GR. After slaughter, the measurements equivalent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 35 publications
8
35
5
2
Order By: Relevance
“…Similar results were reported for SBFT in other breeds (Karya, Karacabey Merino and Kivircik) reared in Turkey (Cemal et al, 2007;Yilmaz et al, 2014). Mean of MD in this study was lower than the mean values reported in some meat-type breeds (Theriault et al, 2009;Slosarz et al, 2011). This was most probably due to the fact that measurements were taken at a relatively early age as part of our breeding program compared with other breeding programs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were reported for SBFT in other breeds (Karya, Karacabey Merino and Kivircik) reared in Turkey (Cemal et al, 2007;Yilmaz et al, 2014). Mean of MD in this study was lower than the mean values reported in some meat-type breeds (Theriault et al, 2009;Slosarz et al, 2011). This was most probably due to the fact that measurements were taken at a relatively early age as part of our breeding program compared with other breeding programs.…”
Section: Discussionsupporting
confidence: 89%
“…The mean of BFT measurements is within the range of values reported by various researchers (Cemal et al, 2007;Theriault et al, 2009;Slosarz et al, 2011;Esquivelzeta et al, 2012;Santos et al, 2014). Similar results were reported for SBFT in other breeds (Karya, Karacabey Merino and Kivircik) reared in Turkey (Cemal et al, 2007;Yilmaz et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Supporting the current results, various authors have noted high positive correlations of UFT with live weight (7,22,23,28), cold carcass weight, bone amount (10), and meat amount (2,10). The fact that UFT measured from both regions in this study had a high correlation with live weight, warm carcass weight, cold carcass weight, and bone and meat amounts means that UFT may be used for a primary estimation of carcass traits (4,9). It was also reported by Agamy et al that ULW values have a significant positive correlation with live weight (7); the same was reported for cold carcass weight by Ripol et al (10).…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, several works have been published that clearly show that the RTU technique allows good estimates of the composition of the carcass to be obtained. These studies aimed to predict carcass composition in adult animals (Hopkins et al ., 2007;Teixeira et al ., 2008), market lambs Leeds et al ., 2008;Orman et al ., 2008;Thériault et al ., 2009;Emenheiser et al ., 2010;Orman et al ., 2010) or light carcasses (Ripoll et al ., 2009). Although the results obtained were generally good, attention must be paid to the factors that lead to inaccuracy in the RTU technique when used for small ruminants.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%